Tranexamic Acid as a Successful Therapy in Turner Syndrome With Recurrent Overt Gastrointestinal Bleeding due to Small Intestinal Venous Anomalies. Issue 1 (20th January 2023) - Lertwilaiwittaya, Pongtawat; Weber, Frederick H.
ABSTRACT: Small intestinal venous abnormalities are an underrecognized condition as an etiology of overt gastrointestinal (GI) bleeding in patients with Turner syndrome. Evidence-based therapeutic options for these lesions are lacking in the published literature. A 47-year-old woman with Turner syndrome with a 30-year course of recurrent GI bleeding was found to harbor diffuse small intestinal venous ectasias through endoscopic imaging. Achievement of a 21-month clinical remission (elimination of hospitalizations for overt GI bleeding and normalization of hemoglobin concentration) was reached after initiation of tranexamic acid titrated to 2, 600 mg daily.